Time-Dependent Variations of Accretion Disk - Hye-Weon Na; Kyung-Mee Kim; Kyu-Hong Choi (Journal of Astronomy and Space Sciences, 1987)
In dward nova we assume the primary star as a white dwarf and the secondary as the late type star which filled Roche lobe. Mass flow from the secondary star leads to the formation of thin accretion disk around the white dwarf. We use the α parameter as viscosity to maintain the disk form and propose that the outburst in dwarf nova cause the steep increase of source term. With these assumptions we solve the basic equations of stellar structure using Newton-Raphson method. We show the physical parameters like temperature, density, pressure, opacity, surface density, height and flux to the radius of disk. Changing the value of α, we compare several parameters when mass flow rate is constant with those of when luminosity of disk is brightest. At the same time, we obtain time-dependent variations of luminosity and mass of disk. We propose the suitable range of α is 0.15-0.18 to the difference of luminosity. We compare several parameters of disk with those of the normal late type stars which have the same molecular weight of disk is lower. Maybe the outburst in dwarf nova is due to the variation of the α value instead of increment of mass flow from the secondary star.